2018
DOI: 10.1007/s00425-018-2956-0
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in plants

Abstract: Attenuation in the activity of the negative regulators or the hyperactivity of plant innate immune receptors often causes ectopic defense activation manifested in severe growth retardation and spontaneous lesion formations, referred to as autoimmunity. In this review, we have described the cellular and molecular basis of the development of autoimmune responses for their useful applications in plant defense. Plants are exposed to diverse disease-causing pathogens, which bring infections by taking over the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 129 publications
0
36
0
Order By: Relevance
“…In animals, NLRs play a role in developmental processes, such as spermatogenesis and fertility, suggesting a control of the reproductive system by NLR proteins (Meunier and Broz, 2017). In plants, inappropriate activation of NLRs caused by mutations or incompatible combinations also impacts development (Chae et al, 2014;Chen et al, 2016;Atanasov et al, 2018;Chakraborty et al, 2018). The integrated decoy model predicts an important role of IDs in pathogen detection.…”
Section: Nlr-ids: Toward the Elucidation Of Additional Nlr Functions?mentioning
confidence: 99%
“…In animals, NLRs play a role in developmental processes, such as spermatogenesis and fertility, suggesting a control of the reproductive system by NLR proteins (Meunier and Broz, 2017). In plants, inappropriate activation of NLRs caused by mutations or incompatible combinations also impacts development (Chae et al, 2014;Chen et al, 2016;Atanasov et al, 2018;Chakraborty et al, 2018). The integrated decoy model predicts an important role of IDs in pathogen detection.…”
Section: Nlr-ids: Toward the Elucidation Of Additional Nlr Functions?mentioning
confidence: 99%
“…Considering these observations, we propose that some R proteins contribute to defense activation in topp4‐1 . Numerous studies have demonstrated that the autoimmune response is caused by excessive and improper activation of R proteins (Chakraborty et al ). Consequently, we speculate that autoimmunity in topp4‐1 is also a result of hyper‐activation of R proteins, and that high temperature recovers the immune‐related phenotype in topp4‐1 possibly through affecting the activation of R proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mutation of a 'guardee' may mimic the presence of a pathogen, and activate the guarding R protein, resulting in an autoimmune phenotype (47). It is therefore reasonable to speculate that grass Gb proteins function as immune guardees.…”
Section: Discussionmentioning
confidence: 99%